PERSEPSI MAHASISWA UNIVERSITAS SAM RATULANGI TENTANG KEBIJAKAN UANG KULIAH TUNGGAL - Rambing, Patrick Nicolas; Rorong, Arie Junus; Palar, Novie (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: This study aims to determine the perception of students of Sam Ratulangi University on thepolicy of Single Tuition. This research was conducted by using qualitative descriptive method. The resultsshowed that: The perceptions formed from each individual student vary based on what is heard, seen, felt andunderstood about Single Tuition. The Single Tuition Policy at Unsrat is very helpful for people who haveeconomic problems to continue the lecture lecture, and easier to manage tuition expenses for students fromearly entry until graduation, and minimize the occurrence of corruption, collusion, and nepotism practice inHigher Education. Student perceptions about the application of Single Tuition at Sam Ratulangi University havenot been fully effective, where the implementation is still not in accordance with the regulation, because thereare still weaknesses in lecturing process, such as: Not exactly the tariff stipulation of Single Tuition charged byevery student because nepotism in the early negotiations to register lectures, inadequate facilities such as labsand classes that are not worth using, Budget for frequent late Lab fees resulting in late lab work in the course,and still found illegal levies in lectures that are detrimental to students. Efforts to be taken to overcome theproblems are found in the application of the Single Tuition policy at Sam Ratulangi University such as: Thelevel of supervision should be considered at the beginning of the negotiations conducted by the providers ofSingle Tuition, the validity of the student's economic date is correct, the Single Tuition Fund Management mustbe transparent, and the effect on the person who commits the violation must be considered and improved.Keywords: Perception, Single Money Policy